Ilusi Virtual: Kejayaan Media atas Audien? Telaah Kritis atas Teori Resepsi Media Jean Baudrillard - Irawanto, Budi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1998)
This article aims to scruntinize more closely Jean Baudrillard work on media reception. This work is important because Jean Baudrillard is one of the most stimulating and provocative contemporary thinker. In his views, similar in some respects to John Fiskes , consumers (audiences) do resist the media. Far from claiming that media reception is passive and alienated, Baudrillard sees in some reception a resistive response to the media. When understood in the light of media reception perspective, both Baudrillard and Fiske have significant contributions to making the theory of mass communication.